La política exterior de México hacia Centroamérica, 1906-1908 - Nava Ortiz, Juana (Universidad Michoacana de San Nicolás de Hidalgo, 2005)
Our country and their neighbors of the south are united by their geographical vicinity and for significant knots of cultural, ethnic and historical identity. However, their relationships have been complex, and they have been studied a little.1 of there the interest of carrying out a study focused to the Mexican foreign policy toward the countries of Central America, 2 specifically that of the last years of the porfiriato. It fits to point out that there are some academics that carry out the chronological cut in 1906, year in that Mexico and Guatemala signed a bordering definitive agreement that leaves aside other transcendental events of the Mexican foreign policy that were raised in that same year, as the participation of Mexico and United States, in mediators' quality, in the warlike conflict between Guatemala and El Salvador. Therefore we consider necessary to study the Mexican performance in favor of an agreement of peace, since Central America was a region in the one that the president Porfirio Díaz, for the grade of reached development of the country, wanted to project the achievements of the régime. Besides to consolidate their regional leadership and to serve as guide and protective of an area with the one that shared frontier.4 this influence ended up being bigger in El Salvador, product of its political vulnerable position in the isthmus and of the necessity of having the protection and support of a stronger country that it could defend it in the event of requiring it.

Nuestro país y sus vecinos del sur están unidos por su vecindad geográfica y por significativos lazos de identidad cultural, étnica e histórica. Sin embargo, sus relaciones han sido complejas, y se han estudiado poco.1 De ahí el interés de realizar un estudio enfocado a la política exterior mexicana hacia los países de Centroamérica, 2 específicamente la de los últimos años del porfiriato. Cabe señalar que hay algunos académicos que realizan el corte cronológico en 1906, año en que México y Guatemala firmaron un acuerdo limítrofe definitivo que deja de lado otros sucesos transcendentales de la política exterior mexicana que se suscitaron en ese mismo año, como la participación de México y Estados Unidos, en calidad de mediadores, en el conflicto bélico entre Guatemala y El Salvador. Por tanto consideramos necesario estudiar la actuación mexicana a favor de un acuerdo de paz, dado que Centroamérica era una región en la que el presidente Porfirio Díaz, por el grado de desarrollo alcanzado del país, quería proyectar los logros del régimen. Además de consolidar su liderazgo regional y servir de guía y protector de una zona con la que compartía frontera.4 Esta influencia llegó a ser mayor en El Salvador, producto de su vulnerable posición política en el istmo y de la necesidad de contar con la protección y apoyo de un país más fuerte que lo pudiera defender en caso de requerirlo.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2005-0005; Opción en historia de América; Política exterior; México; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2350